D??diva e APP: doa????o na perspectiva de aplicativos sociais - Godinho, Sibele Grasiela Guedes (2016)
This research considers the potential motivations of using a social app for the realization of donations and probe the symbolic interactions that occur during solidarity exchanges mediated by technology. Smartphones and their applications are inseparable increasingly part of the daily lives of people who spend all their time with their devices: always on, always connected, as close as the shirt itself. Applications for mobile devices -apps- are the software installed in these smartphones that perform or assist in performing tasks for their users. Among the tools that the various types of apps present, there is a category of social apps, which are those facing a social cause. The conducted study noted when addressing the social application Solidarius, created for realization of donations to the group of welfare Sociedade S??o Vicente de Paulo, Vicentinos, which by enabling the realization of solidarity mediated by technology, materializes a new type of solidarity , anonymous, but allows the existence of a link, which excludes the direct involvement with people in common vulnerability in voluntary actions, but allows the user a sense of belonging, even if momentarily, to a larger institution or cause himself, and generate feelings of satisfaction and gratitude. These observations were made possible by the bibliography study published on the subject, the data analysis and information gathered during interviews with the developers of social application on screen and representatives of the institution that it will use, and the above discussion in focus group held with potential users of the application. As a result, to be detailed in subsequent research, it was realized that social applications allow its users an empowerment, regarding the perception that are interfering with reality and contributing to a cause, and that the technology of apps, for convenience, ease and closeness they have with the user, can be instruments of social change.